附加非线性阻尼夹层的间隙弹性机构减振分析 - 王国庆; 左建昌; 王帑; 刘宏昭 (Jixie chuandong)
It is presented to realize the low cost vibration control that method of adhering nonlinear damping alloy constraint layer partly to the component of mechanism with clearance joints.The nonlinear spring damping contact model is adopted to describe the contact force of the clearance joint elements,based on it,the dynamic model of the crank rocker mechanism with clearance joints is established.By using curve fitting describe the rule of the dissipation factor of damping alloy changing with stress and taking account of the sheared,the nonlinear constitutive relation was given depending on the stress and strain base on the equivalent viscous damping theory,then deduced a type of composite element model with two nodes and ten degrees of freedom,which had the characteristics of nonlinear damping and structural damping,established the dynamic model of the elastic mechanism partly adhering nonlinear damping alloy constraint layer.The methods presented are feasible by numerical simulation.